Business Intelligence in Thailand's Higher Educational Resources Management - Sirawit Kleesuwan; Somsak Mitatha; Preecha P. Yupapin; Bunjong Piyatamrong (My University, 2010)
Abstract For the past decade, Thailand's higher education has been expanded beyond the resources funded by The Office of the Higher Commission. There were 76 public universities and 68 private universities and 19 community colleges served about 1.75 million students in both the undergraduate and graduate levels in 2008. To make an effective and efficient resource allocation, the Business Intelligent (BI) was deployed to generate executive decision support information for the management. This paper illustrated the roles of BI in Thailand's higher education resource management, the implementation, the technology, and the key succeed factors. The security concept is employed in this work based on web browser technology.
Keywords: Business Intelligence; Big Data and Business Intelligence